Characteristics and potential development strategy for coastal women in the management of coastal resources in Manado City - Rondonuwu, Deyne; Paruntu, Carolus P; Erens, Kaparang; Budiman, Johnny (Universitas Sam Ratulangi, 2013)
Characteristics and potential of women for coastal development strategies in the management of coastal resources in the coastal city of Manado were studied. The characteristic components of coastal women who participated, included: (1) the composition of coastal women based on the total number of inhabitants, level of education and type of employment, (2) women's income as a contribution to the family income of coastal fishermen, (3) the portion of government budget earmarked for women's empowerment in coastal areas, and (4) coastal women's participation in educational activities and training. The study formulated five women's potential coastal development strategies through SWOT analysis, namely: (1) managing coastal resources sustainably by coastal women, (2) increasing access to capital for the business development of coastal women, (3) increasing government budget allocations for coastal women's empowerment, (4) improving the education and skills of coastal women, (5) women's empowerment in the development of coastal area reclamation, waste management and the improvement of the quality of fishery commodities and handicrafts. The results of this study showed that the women in the coastal city of Manado as resource managers are one of the great development potentials. However, this has not been well managed strategically and developed by the Government. It is recommended to Manado City Government to be more focused on empowering coastal women in the management of coastal resources for the well-being of coastal communities and fishermen. Karakteristik dan strategi pengembangan potensi perempuan pesisir dalam pengelolaan sumber daya pesisir di enam kelurahan pesisir Kota Manado, yaitu: Kelurahan Bunaken, Tumumpa II, Tongkaina, Malalayang I Timur, Wenang Selatan dan Sario Utara dikaji. Komponen karakteristik perempuan pesisir yang diuji, meliputi: (1) komposisi perempuan pesisir berdasarkan jumlah total jiwa, tingkat pendidikan dan jenis pekerjaan, (2) kontribusi pendapatan perempuan pesisir terhadap pendapatan keluarga nelayan, (3) besarnya bantuan pemerintah dalam APBD terhadap pemberdayaan perempuan pesisir, dan (4) partisipasi perempuan pesisir dalam kegiatan pendidikan dan pelatihan. Ada lima strategi pengembangan potensi perempuan pesisir melalui analisis SWOT, yaitu: (1) mengelola sumber daya pesisir yang berkelanjutan berbasis perempuan pesisir, (2) meningkatan akses permodalan bagi pengembangan usaha perempuan pesisir, (3) meningkatkan alokasi APBD Pemerintah untuk pemberdayaan perempuan pesisir, (4) meningkatkan pendidikan dan ketrampilan perempuan pesisir, (5) memberdayakan perempuan pesisir dalam pembangunan kawasan reklamasi pantai, pengelolaan sampah dan peningkatan kualitas komoditi hasil perikanan dan kerajinan. Hasil kajian memperlihatkan bahwa perempuan pesisir Kota Manado dalam pengelolaan sumber daya pesisir merupakan salah satu potensi sumber daya yang besar, namun belum dikelola dan dikembangkan secara strategis oleh Pemerintah. Untuk itu disarankan kepada Pemerintah Kota Manado agar lebih fokus dalam membangun perempuan pesisir dalam pengelolaan sumber daya pesisir untuk kesejahteraan masyarakat pesisir dan nelayan.